1973
DOI: 10.1161/01.res.32.6.712
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of Renal Blood Flow on Prostaglandin Synthesis in the Dog

Abstract: Inhibition of prostaglandin synthesis in chloralose-anesthetized dogs reduced renal blood flow, and this reduction closely correlated (r = 0.92, P<0.01) with a decline in the renal efflux of a substance having the properties of PGE 2 . We used solvent extraction and thin-layer chromatography coupled with parallel bioassay to identify and assay the PGE-and PGF-like substances (expressed as PGE 2 and PGF 2a equivalents). Either of two antunflaiunatory acids, indomethacin or meclofenamate, that inhibited conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1
1

Year Published

1975
1975
1984
1984

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(60 citation statements)
references
References 18 publications
2
56
1
1
Order By: Relevance
“…Although we had no direct measurement of renal prostaglandin synthesis there is evidence that the doses of indomethacin used here were sufficient to reduce prostaglandin synthesis (Vane, 1971;Ferreira, Moncada & Vane, 1971). Indomethacin, in doses less than those used in the present experiments, has been shown to reduce significantly the efflux of prostaglandins into dog renal venous blood (Aiken Herbaczynska-Cedro & Vane, 1973;Lonigro, Itskovitz, Crowshaw & McGiff, 1973) and to enhance the vasoconstriction caused by angiotensin, which normally promotes prostaglandin release in the absence of indomethacin. Indomethacin abolishes the conversion of labelled arachidonic acid to prostaglandins in homogenates of rabbit kidney (Larsson & Angaard, 1973), and reduces urinary efflux of prostaglandins by 40 %.…”
Section: Discussionmentioning
confidence: 65%
“…Although we had no direct measurement of renal prostaglandin synthesis there is evidence that the doses of indomethacin used here were sufficient to reduce prostaglandin synthesis (Vane, 1971;Ferreira, Moncada & Vane, 1971). Indomethacin, in doses less than those used in the present experiments, has been shown to reduce significantly the efflux of prostaglandins into dog renal venous blood (Aiken Herbaczynska-Cedro & Vane, 1973;Lonigro, Itskovitz, Crowshaw & McGiff, 1973) and to enhance the vasoconstriction caused by angiotensin, which normally promotes prostaglandin release in the absence of indomethacin. Indomethacin abolishes the conversion of labelled arachidonic acid to prostaglandins in homogenates of rabbit kidney (Larsson & Angaard, 1973), and reduces urinary efflux of prostaglandins by 40 %.…”
Section: Discussionmentioning
confidence: 65%
“…Studies from this and other laboratories have demonstrated that PG synthesized intrarenally will affect blood flow to the cortex, chiefly that to the juxtamedullary nephrons (29,34). As the synthesis of PG in the kidney occurs almost entirely in the medulla (35), the question arises as to how the PG are transported from medulla to the point of blood flow regulation in the cortex.…”
Section: Human Studiesmentioning
confidence: 96%
“…In previous studies evaluating the renal circulation, Lonigro, Itskovitz, Crowshaw, and McGiff and Kirschenbaum, White, Stein, and Ferris, both noted a decrease in renal blood flow after the administration of meclofenamate or indomethacin (13,14). In addition, in the former study, there was a profound fall in renal venous PGE levels as measured by bioassay techniques.…”
Section: Discussionmentioning
confidence: 92%